Structure fragmentation in Fe-based alloys by means of cyclic martensitic transformations of different types - Bondar, Volodimir I (Springer, 2014)
The effect of martensite transformations of different types on the misorientation of austenite crystalline lattice, which characterizes the degree of structure fragmentation, was investigated for Fe-Ni and Fe-Mn alloys. As a result of multiple face-centered cubic (f.c.c.)-body-centered cubic (b.c.c.)-f.c.c. transformations, an austenite single-crystalline specimen is transformed in a polycrystalline one due to progressive fragmentation. It was shown that the degree of fragmentation depends on the magnitude of volume change and the density of dislocations generated on martensitic transformations.